Resolução do problema de carregamento e descarregamento de contêineres em terminais portuários via Beam Search - Lima, Fábio Mascagna Bittencourt [UNESP] (2011)
One problem that has been happening frequently in port terminals is the poor planning of the loading and unloading of containers. The reason of this problem is the lack of an efficient method that provides the best means of these operations. The main goal of this work is, to implement a method that provides the best ways to perform the loading and unloading of containers, at each port and thus bring a great saving for these terminals, since the number of moves is directly proportional to cost. To carry out this program was used the idea that the containers are placed in vertical stacks, where the access can be done only by the top of the stack, so the ship was treated as an matrix and to fill it, two rules were created for loading and two for unloading. To obtain the best sequence of rules was used Beam Search method, which is an enumeration type implicit method that analyzes only the best solution of the tree generated. Thus, the program developed in the Java language, provides the best way to perform the loading and unloading ports and the way as the ship leaves each port using a graphical interface